Evaluation of the Effect of Surfactants on the Adsorption and Movement of Carbaryl in Soils of Divergent Texture - Rishi P. Singh; Syed A. Nabi; Sujata Singh (Adsorption Science & Technology)
The adsorption and movement of carbaryl on soils in surfactant-free and surfactant (cationic, non-ionic, anionic) solutions of different critical micelle concentrations (CMCs) has been studied using batch equilibrium and soil thin layer chromatography (soil TLC) techniques. The adsorption of carbaryl in surfactant–soil–water systems followed the order cationic > anionic > non-ionic as anticipated from the Freundlich constant, K F , and distribution coefficient, K D , values. The R f values obtained from soil TLC studies were inversely proportional to the K F and K D values. The affinities of carbaryl towards organic carbon and the clay content of the soil were compared using the K OC and K C values. The behaviour of carbaryl in surfactant–soil–water systems mainly depends on the degree of hydrophobicity of the pesticide and the type and concentration of surfactant used. The K D */K D ratios were used to evaluate the remediation efficiency of surfactants and it was found that anionic surfactant is a better choice for remediation of contaminated soils. The remediation efficiency of non-ionic surfactant varies with the nature of the soils whereas cationic surfactant leads to poor remediation efficiency. The results obtained are interesting as they afford the basic data relating to the possible use of surfactants for solving pollution problems posed by carbaryl.